2019
DOI: 10.1055/s-0039-1681013
|View full text |Cite
|
Sign up to set email alerts
|

How does Fetal Autopsy after Pregnancy Loss or Termination for Anomalies and other Complications Change Recurrence Risk?

Abstract: Objective  Historically, fetal autopsy was common after terminations for anomalies. Previous studies report that fetal autopsy confirms ultrasound findings in the majority of cases. This study aims to examine correlation between prenatal and autopsy diagnoses at University of California, San Francisco (UCSF) and evaluate whether autopsy adds diagnostic information, specifically information that changes risk of recurrence for future pregnancies. Study Design  We conducted a retrospective chart review of all fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 24 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…and in recurrence risk (3.9%, particularly for neurologic, genitourinary, and multiple anomalies) based on autopsy findings. 4 In fact, although several studies including fetuses from all gestational weeks, spontaneous abortions, and neonatal deaths emphasized a strong correlation between ultrasound and autopsy, 4,5 the studies specifically included fetal malformations detected at prenatal ultrasound in second-trimester termination of pregnancy and revealed discrepancies between ultrasound and autopsy findings in about 40% of cases, emphasizing the importance of autopsy examination after every termination of pregnancy. 3,10,11 In particularly, in a systematic review of 19 studies with 3534 fetuses on the correlation between fetal autopsy and ultrasound findings of fetal malformations that resulted in pregnancy terminations, the authors reported that autopsy findings confirmed prenatal ultrasound in 2401 (68.0%) fetuses, provided additional information in 794 (22.5%) fetuses, and did not confirm prenatal ultrasound in 329 (9.2%) fetuses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…and in recurrence risk (3.9%, particularly for neurologic, genitourinary, and multiple anomalies) based on autopsy findings. 4 In fact, although several studies including fetuses from all gestational weeks, spontaneous abortions, and neonatal deaths emphasized a strong correlation between ultrasound and autopsy, 4,5 the studies specifically included fetal malformations detected at prenatal ultrasound in second-trimester termination of pregnancy and revealed discrepancies between ultrasound and autopsy findings in about 40% of cases, emphasizing the importance of autopsy examination after every termination of pregnancy. 3,10,11 In particularly, in a systematic review of 19 studies with 3534 fetuses on the correlation between fetal autopsy and ultrasound findings of fetal malformations that resulted in pregnancy terminations, the authors reported that autopsy findings confirmed prenatal ultrasound in 2401 (68.0%) fetuses, provided additional information in 794 (22.5%) fetuses, and did not confirm prenatal ultrasound in 329 (9.2%) fetuses.…”
Section: Discussionmentioning
confidence: 99%
“…Technical advancements in imaging techniques have enabled high‐resolution prenatal ultrasonography with a higher diagnostic accuracy in detection rate of fetal malformations 1–4 . Nonetheless, in pregnancy terminations based on prenatal prediction of fetal anomalies, fetal autopsy is important in terms of assessing the quality and accuracy of prenatal ultrasound findings on fetal anomaly as well as for the potential implications of detected malformations for future pregnancies 1–4 . Hence, a prenatal ultrasound examination and a subsequent detailed fetal autopsy provide the basis for a correct diagnosis in pregnancies terminated because of congenital anomalies; fetal autopsy is regarded as the reference standard for assessing the accuracy of prenatal ultrasound 3,5–8 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations